2012
DOI: 10.1093/hmg/dds293
|View full text |Cite
|
Sign up to set email alerts
|

Preventing phosphorylation of dystroglycan ameliorates the dystrophic phenotype in mdx mouse

Abstract: Loss of dystrophin protein due to mutations in the DMD gene causes Duchenne muscular dystrophy. Dystrophin loss also leads to the loss of the dystrophin glycoprotein complex (DGC) from the sarcolemma which contributes to the dystrophic phenotype. Tyrosine phosphorylation of dystroglycan has been identified as a possible signal to promote the proteasomal degradation of the DGC. In order to test the role of tyrosine phosphorylation of dystroglycan in the aetiology of DMD, we generated a knock-in mouse with a phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 48 publications
2
50
1
Order By: Relevance
“…Alternative proteins that may anchor these dystroglycan complexes include ankyrins and plectins that can bind directly to β-dystroglycan [67,68]. We have previously detected ankyrin in dystroglycan immunoprecipitations from mdx muscles [31] and association of dystroglycan with plectins can be modulated by tyrosine phosphorylation of the β-dystroglycan intracellular domain leading to amelioration of the mdx phenotype [15]. Although intracellular binding partners of dystroglycan that are distinct from dystrophin and utrophin likely exist in muscle, our data suggest that these interactions may be affected by loss of dystrophin in mdx muscle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative proteins that may anchor these dystroglycan complexes include ankyrins and plectins that can bind directly to β-dystroglycan [67,68]. We have previously detected ankyrin in dystroglycan immunoprecipitations from mdx muscles [31] and association of dystroglycan with plectins can be modulated by tyrosine phosphorylation of the β-dystroglycan intracellular domain leading to amelioration of the mdx phenotype [15]. Although intracellular binding partners of dystroglycan that are distinct from dystrophin and utrophin likely exist in muscle, our data suggest that these interactions may be affected by loss of dystrophin in mdx muscle.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental evidence stems from the observation that loss of dystrophin in mice ( mdx ) and humans (DMD) leads to a dramatic decrease in dystroglycan expression at the myofiber membrane [1,1517]. The residual dystroglycan is believed to interact with utrophin, a homolog of dystrophin whose expression is normally restricted to the neuromuscular junction (NMJ) in adult muscles [1820].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, accumulation of dystroglyan, independent of other treatments, has also been shown to decrease disease severity in dystrophic skeletal muscle (34). Improved resistance to damage caused by lengthening contractions indicates that the DAPC components are not only increased but also are functioning.…”
Section: R19mentioning
confidence: 99%
“…Previous studies demonstrated that preventing tyrosine phosphorylation of β-Dg in mdx mouse alleviated the dystrophic phenotype in a genetic mouse model, ameliorating many of the main pathological symptoms associated with dystrophin deiciency [78]. The use of dasatinib was found to decrease β-Dg phosphorylation levels in tyrosine and to increase the relative levels of nonphosphorylated β-Dg in the sapje zebraish, improving its physical condition [79].…”
Section: Dg In Cell Membrane Organizationmentioning
confidence: 98%
“…Additional modiications to β-Dg, however, include phosphorylation on tyrosine [75,76] and speciic proteolytic cleavage events. Tyrosine phosphorylation of β-Dg serves as a molecular switch to regulate the binding of diferent cellular-binding partners [77], but it is also a signal of the internalization of Dg from the plasma membrane [78,79] and may mediate some proteolytic events and nuclear translocation [80,81].…”
Section: Dg and Its Postranscriptional Modiicationsmentioning
confidence: 99%